From 'mad honey' to hypotensive agents, the grayanoid diterpenes. (1st September 2016) - Hanson, James
The toxicity of Rhododendron species and other members of the Ericaceae which is due to the grayanoid diterpenes, is described. Their structures, biogenesis and biological activity is reviewed.